PRAME and WT1 transcripts constitute a good molecular marker combination for monitoring minimal residual disease in myelodysplastic syndromes. Issue 7 (1st July 2013) - Qin, Ya-Zhen; Zhu, Hong-Hu; Liu, Yan-Rong; Wang, Ya-Zhe; Shi, Hong-Xia; Lai, Yue-Yun; Xu, Lan-Ping; Liu, Dai-Hong; Jiang, Qian; Li, Ling-Di; Jiang, Bin; Liu, Kai-Yan; et al.
Abstract: PRAME and WT1 transcript levels were simultaneously measured in 312 bone marrow samples collected from patients with newly diagnosed myelodysplastic syndromes (MDS) and 111 samples collected during the treatment of 17 patients. Both the positive rate and the > 1-log increase expression frequency of PRAME were similar to those of WT1 (74.4 % vs. 77.6%; 51.6% vs. 49.0%), and 88.1% of patients overexpressed at least one marker. Moreover, the frequencies of PRAME expression with higher degrees of increase were significantly higher compared with those of WT1 expression (> 2-log increase: 30.8% vs. 3.8%; > 3-log increase: 9.0% vs. 0%; all p < 0.001). PRAME had a higher log increase than WT1 in 53.3% of the patients with overexpressed WT1. Both PRAME and WT1 transcript levels generally fluctuated within the normal range after hematopoietic stem cell transplant in all 10 patients in continuous complete remission. Six out of seven patients were predicted relapse by the combined detection: sustained positivity, or significant increase to be positive for both WT1 and PRAME in three patients, earlier by PRAME than WT1 or by PRAME alone in three patients. Thus, PRAME and WT1 transcripts constitute a good molecular marker combination for monitoring minimal residual disease in MDS.